Inverse Association Between Neck Pain and All-Cause Mortality in Community-Dwelling Older Adults. Issue 12 (6th December 2017) - Muscari, Antonio; Bianchi, Giampaolo; Forti, Paola; Magalotti, Donatella; Pandolfi, Paolo; Zoli, Marco; ,
Abstract: Objective: In a previous study, we found an apparent protective effect of neck pain on all-cause mortality in subjects older than age 85 years. The present longitudinal investigation was performed to verify this unexpected finding in a larger sample and to establish its significance. Design: Population follow-up study. Setting: Three towns of Northern Italy. Subjects: We examined 5, 253 community-dwelling residents age 65–102 years (55% female). Methods: Through a postal questionnaire, baseline information was obtained concerning cardiovascular risk factors, self-rated health, physical activity, cardiovascular events, medical therapy, and presence of pain in the main joints. Seven-year all-cause mortality was the end point. Results: During follow-up, 1, 250 people died. After adjustment for age, sex, anti-inflammatory drugs, physical activity, and main risk factors, neck pain was inversely associated with mortality (hazard ratio = 0.74, 95% confidence interval = 0.64–0.86, P  < 0.001). This association was present, with high significance, in each of the eight following subgroups: men, women, age 65–74 years, age 75–84 years, age ≥85 years and residents of each of the three towns. The subjects without neck pain (N = 3, 158) were older, more often men, less often hypercholesterolemic, less physically active, and had more frequently had a stroke than the subjects with neck pain (N = 2, 095). There were no differences in the causes of death between subjects with or without neck pain. Conclusion: This study has confirmed the existence of an independent inverse association between neck pain and mortality in the elderly, suggesting that reduced sensitivity to neck pain may be a new marker of frailty.